2007
DOI: 10.1210/en.2007-0358
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Improves Reversal of Diabetes in NOD Mice Treated with Anti-CD3 Monoclonal Antibody by Enhancing Recovery of β-Cells

Abstract: Immune modulators can arrest loss of insulin secretion in type 1 diabetes mellitus (T1DM), but they have not caused permanent disease remission or restored normal insulin secretion. We tested whether exendin-4, a glucagon-like peptide-1 receptor agonist, would enhance remission of T1DM in NOD mice treated with anti-CD3 monoclonal antibody (mAb) and studied the effects of exendin-4 treatment on cellular and metabolic responses of beta-cells. Diabetic NOD mice treated with anti-CD3 mAb and exendin-4 had a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
118
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(127 citation statements)
references
References 34 publications
7
118
1
1
Order By: Relevance
“…Continuous infusion of GLP-1 also delayed the onset of diabetes in NOD mice [30]. Other studies have used exendin-4 in combination with anti-inflammatory agents to demonstrate a more significant blocking of insulitis and diabetes onset in NOD mice [31][32][33]. Furthermore, a recent study has reported that increasing the levels of circulating GLP-1 by inhibiting dipeptidyl peptidase-IV results in prolonged islet graft survival and decreased insulitis in diabetic NOD mice [34].…”
Section: Discussionmentioning
confidence: 96%
“…Continuous infusion of GLP-1 also delayed the onset of diabetes in NOD mice [30]. Other studies have used exendin-4 in combination with anti-inflammatory agents to demonstrate a more significant blocking of insulitis and diabetes onset in NOD mice [31][32][33]. Furthermore, a recent study has reported that increasing the levels of circulating GLP-1 by inhibiting dipeptidyl peptidase-IV results in prolonged islet graft survival and decreased insulitis in diabetic NOD mice [34].…”
Section: Discussionmentioning
confidence: 96%
“…It is conceivable that residual beta cells are lost because the autoimmune reactivity had only been transiently suppressed; their survival and/or function may also have been affected by the chronic state of hyperglycaemia. Since the beta cell mass is already markedly reduced at clinical onset of type 1 diabetes [18,19], it is likely that any immune-modulating intervention will have to be associated with, or followed by, a beta cell replacement therapy, as recently tested in rodents [20]; a combination with other methods for tolerance-induction should also be considered [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 5 have demonstrated that continuous infusion of GLP-1 in pre-diabetic NOD mice results in significant delay in the onset of diabetes as a result of increased beta-cell proliferation coupled with decrease in beta-cell apoptosis. Furthermore, combination therapies using GLP-1 or exendin-4 with gastrin, 48 anti-lymphocyte serum 49 or anti-CD3 immunotherapy 50 have been shown to restore normoglycemia in acutely diabetic NOD mice by increasing insulin stores and reducing beta-cell apoptosis. Thus, GLP-1-receptor agonists may be useful in therapeutic management of individuals with either type-1 or type-2 diabetes.…”
Section: Discussionmentioning
confidence: 99%